Christian mission, contextual theology, prophetic dialogue : essays in honor of Stephen B. Bevans, SVD - Irvin, Dale T., 1955-; Phan, Peter C., 1943-; Bevans, Stephen B., 1944- (Maryknoll, NY, Orbis Books, 2018)
"While the intent of the editors is to honor Steve Bevans, SVD, a towering figure in the field of missiology and a longtime author of Orbis books on missiology, this book will be designed less as a festschrift than as a textbook for classroom use. Designed around the three main foci of Bevans' theology (mission, contextual theologies, and dialogical theory), it will appeal to teachers of courses in Christian mission, theological method, contextual theologies, and contemporary Third World theologies. The contributors are a who's who of contemporary mission studies in a global context, including representatives from various Christian traditions and from throughout the global church"--
The final testimony of Missio Dei : a missiological reading of revelation / Vanthanh Nguyen -- Mission in Roman Catholic theology / Roger Schroeder -- Mission in Orthodox theology / Athanasios N. Papathanasiou -- Mission in Protestant theology / Dale T. Irvin -- Mission in Pentecostal theology / Veli-Matti Karkkainen -- Contexts and theological models / Robert Schreiter -- From ecclesiology in Europe to contextual theology for the world / Thomas O'Meara -- Christian theology, empire, and race in North America : in honor of Stephen Bevans / Leo D. Lefebure -- Doing theology in world Christianity : new paths, different themes, strange locations / Peter C. Phan -- Christianity interrupted: liberation theology's past, present, and future through the lens of rupture / Gemma Tulud Cruz -- Contextual theology from a cultural perspective / Jose M. de Mesa -- Experience seeking faith : from theology of religions to interreligious theology / Anh Q. Tran -- The church : mission-led ecclesiology for today / Carolyn Chau -- Becoming a global theologian : a personal journey / Stephen B. Bevans.
Includes bibliographical references and index.
Keywords: Missions -- Theory; Christianity and culture